Hierarchical elements for the iterative solving of turbulent flow problems on anisotropic meshes - Wane, B.A.; Urquizaa, J.M.; Fortin, A.; Pelletier, D. (European Journal of Computational Mechanics, 2012)
Accurate solution of industrial turbulent flow problems requires very fine meshes resulting in large systems of non-linear equations and huge computational costs. Efficient iterative methods are therefore necessary. Mesh adaptation, and in particular anisotropic mesh adaptation, allows to reduce considerably meshes size while preserving the accuracy of the solution. Unfortunately, iterative methods and anisotropic meshes do not come along easily and convergence problems may occur. In this work, we show how quadratic elements, expressed in a hierarchical basis, can be used to develop efficient iterative methods for the numerical simulation of turbulent flows on strongly anisotropic meshes.